Redox properties of molten salts for methane activation - Claridge, J; Green, M; Lago, R; Tsang, S; York, A (Baltzer Science Publishers, Baarn/Kluwer Academic Publishers, 1993)
Molten salt mixtures have been tested in a redox mode as catalysts for the activation of methane at 750 °C. It is found that after pre-treatment with dioxygen a transition metal halide/ sodium vanadate melt can convert methane selectively to C2+ products in the absence of molecular oxygen. The melt can be reactivated by passing dioxygen. Electron paramagnetic resonance studies of the quenched samples showed that the transition metal ions are reduced by methane and can be reoxidised by dioxygen. It is also found that higher C2+ selectivity, C2+ yield and C2H4/C2H6 ratio are promoted by added transition metal chlorides and, surprisingly, also by the corresponding metal bromides. It supports the suggestion that surface modification by halogen is more important than gas radical reactions. Comparison of the molten mixtures under redox and cofeed conditions showed that the former gave a higher C2+ selectivity, but no oxygenated products whereas formaldehyde was only detected in the cofeed conditions. © 1993 J.C. Baltzer AG, Science Publishers.